(untitled) (International Seven Journal of Multidisciplinary, 2023)
This research is dedicated to studying the comprehensive analysis of the new legal framework for basic sanitation in Brazil, established by Law 14.026/2020, with a focus on understanding its impacts, challenges and advances in various related areas, such as governance, public health, sustainable development and institutional capacity. Sanitation is a crucial issue for the well-being of the population and the development of the country, involving not only water and sewage infrastructure, but also issues of public health, quality of life, environmental sustainability and social equity. Based on these findings, this work seeks to understand and evaluate the changes introduced by Law 14.026/2020, which reformulated the regulatory framework for basic sanitation in Brazil. The research will be carried out through an in-depth bibliographic review, exploring academic works and official sources that address the theme of basic sanitation and aspects related to the new legislation. It is hoped to obtain an in-depth analysis of the impact of the new basic sanitation legislation, as well as a clearer understanding of the areas that need attention and possible future directions for public policies in the area of sanitation.